2011
DOI: 10.1007/s00360-011-0574-2
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomal activities in the claw muscle tissue of European lobster, Homarus gammarus, during larval development

Abstract: Decapod crustaceans grow discontinuously and gain size through complex molt processes. The molt comprises the loss of the old cuticle and, moreover, substantial reduction and re-organization of muscles and connective tissues. In adult lobsters, the muscle tissue of the massive claws undergoes significant atrophy of 40-75% before ecdysis. The degradation of this tissue is facilitated by calcium-dependent proteases and by the proteasome, an intra-cellular proteolytic multi-enzyme complex. In contrast to the adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…The fraction that we separated by glycerol-gradient centrifugation contained most likely both, the 20S and the 26S population of the proteasome. Previous studies on crustaceans showed that both forms of the proteasome are active under physiological conditions (Mykles, 1998(Mykles, , 1999aGötze and Saborowski, 2011). Therefore, the use of a mixed population of the proteasome appears suitable for our study.…”
Section: Discussionmentioning
confidence: 99%
“…The fraction that we separated by glycerol-gradient centrifugation contained most likely both, the 20S and the 26S population of the proteasome. Previous studies on crustaceans showed that both forms of the proteasome are active under physiological conditions (Mykles, 1998(Mykles, , 1999aGötze and Saborowski, 2011). Therefore, the use of a mixed population of the proteasome appears suitable for our study.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, short fluorophore-labeled peptides are commonly used, which are less specific and can therefore also be targeted by other proteolytic enzymes (Rosser et al, 1993;Garcia et al, 1998;Michael et al, 2005). Of particular importance when preparing crude tissue extracts is avoiding contamination with digestive enzymes from the gut or digestive glands of the animals, which may entirely mask the innate proteasomal activity of the sample (Götze and Saborowski, 2011a;A.B., personal observation). So, when starting work with new species the degree of cross-reactivity needs to be determined in crude extracts of uncontaminated samples.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the proteasome is thought to play an important role in claw muscle degradation during the molting process of adult and larval lobsters (Mykles, 1999b;Götze and Saborowski, 2011a). Bivalves were established as new model organisms to investigate physiological processes such as stress tolerance and ageing (Cherkasov et al, 2006;Ivanina et al, 2008;Philipp and Abele, 2010).…”
Section: Introductionmentioning
confidence: 99%